La comunicación efectiva y su importancia en el desarrollo de competencias lingüísticas del inglés en estudiantes andinos - Vargas, Diana (Instituto Universitario de Innovación Ciencia y Tecnología Inudi Perú, 2023)
The book is an adaptation of an investigation presented to the Universidad Nacional del Altiplano, whose objective was to investigate the impact of effective communication as a didactic method in the development of linguistic skills in English as a third language in students of the School of Professional Technical Higher Education. of the National Police of Peru, Branch Puno (EESTP - PNP - Puno); in order to address the difficulty in learning the English language for Andean students who have Quechua or Aymara as their first language, Spanish as a second language and, due to the addition of current proficiency requirements, English as a third language, focusing on language as a communicative competence that actively assimilates, models and elaborates a base in relation to the current world. For this, we work with two groups of students from the second cycle of studies of the EESTP - PNP - Puno: a control group and an experimental group. The control group consisted of thirty (30) students and the experimental group with twenty-eight (28) students. Initially, both groups took an entrance test; and immediately, only to the experimental group, during the sessions of the English course, effective communication was applied as a didactic strategy to develop the linguistic competences of the English language. After one academic semester, an exit test is taken for both groups. And from a comparison it is concluded that effective communication impacts the linguistic skills of English as a third language in andean students by 91.67%, which is considered within the outstanding achievement.